SIMILARITIES AND DIFFERENCES OF TENSE IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - BERDIYEVA MAYSARA (TADQIQOTLAR.UZ, 2024)
This study examines the similarities and differences in the tense systems of English and Uzbek, two linguistically distinct languages from the Indo-European and Turkic families, respectively. Both languages use tense to convey the time of action, but they diverge significantly in their structures and usage.English tense includes three primary tenses (present, past, and future) and their perfect, continuous, and perfect continuous aspects. It relies heavily on auxiliary verbs and morphological changes to verbs.In contrast, Uzbek employs a more agglutinative structure with a simpler tense system. It uses suffixes to indicate tense and aspect, often combining them in a single verb form. The future tense in Uzbek is less grammatically distinct, sometimes inferred from context rather than explicit forms.Despite these differences, both languages share the fundamental purpose of tenses: to situate actions in time. Understanding these similarities and differences is crucial for language learners and linguists, shedding light on the cognitive and structural aspects of tense usage across different language families.